Inhibitory effects of ethanolic, methanolic, and hydroalcoholic extracts of olive (Olea europaea) leaf on growth, acid production, and adhesion of Streptococcus mutans - Zahra Golestannejad; Faezeh Khozeimeh; Reihaneh Abtahi; Zahra Zarei; Leila Sadeghalbanaei; Rastin Sadeghian (Wolters Kluwer Medknow Publications, 2020)
Background: Usage of chemical mouthwashes for controlling dental caries can end to some side effects such as oral biological imbalance. Recently, using natural derivatives such as herbs, presented to overcome such adverse effects. Due to antibacterial property of olive leaf extracts (Olea europaea), this study conducted in order to evaluate bacteriocidal, anti-acid production, and anti-adhesion effects of olive leaf ethanolic, methanolic, and hydroalcoholic extracts on Streptococcus mutans. Materials and Methods: In this in vitro study, nine strains of S. mutans (PTCC1683) were used. Maceration methods were done in order to provide the olive leaf ethanolic, methanolic, and hydroalcoholic extracts. The antibacterial activities evaluated by macrodilution and disc diffusion method in different concentrations (3.25%-100%). Acid production and adhesion of bacterial strains also were evaluated. The obtained data were analyzed by analysis of variance method using SPSS software. P < 0.05 was considered as statistically significant. Results: The minimum inhibitory concentration and minimum bactericidal concentration for ethanolic, methanolic, and hydroalcoholic olive leaf extracts on S. mutans are 12%-25%, 50%-75%, and 12%-25%, respectively. In addition, inhibition zone of S. mutans significantly increased in higher concentration (ethanolic and methanolic extracts: P = 0.004; hydroalcoholic extract: P = 0.003). The acid production and adhesion significantly decreased by increase in the concentration (P < 0.001). Conclusion: In general, olive leaf ethanolic, methanolic, and hydroalcoholic extracts induce growth inhibition, acid production, and adhesion of S. mutans. Consequently, it can be used as a natural preservative in the food industry, as well as in the production of commercial products such as chewing gum, chocolate, and toothpaste to prevent dental caries.